Vulvovaginal candida in a young sexually active population: prevalence and association with oro-genital sex and frequent pain at intercourse. Issue 1 (30th January 2004) - Rylander, E; Berglund, A-L; Krassny, C; Petrini, B
Abstract : Objective: To study the prevalence of vulvovaginal candida among sexually active adolescents. To determine past and present symptoms, including pain at intercourse and potential behavioural risk factors associated with vulvovaginal candidiasis. Methods: At an adolescent centre, 219 sexually active women who underwent genital examination, also completed a questionnaire on a history of genital symptoms and infections, sexual and hygiene habits, and the use of contraceptives. Symptoms and clinical signs were registered. Vaginal samples were analysed for candida species and urine for Chlamydia trachomatis . Results: Candida culture was positive in 42% of the women and only 15% were asymptomatic. A history of recurrent candidiasis was given by 22%. Frequent pain at intercourse was reported by 24% and frequent oro-genital sex by 42% of the women. Frequent pain at intercourse was significantly associated with both the growth of candida and a history of recurrent candidiasis. Oro-genital sex was an independent risk factor for the growth of candida. Conclusion: In sexually active adolescents, who underwent genital examination, candida cultures were positive in 42%. The habit of frequent oro-genital sex was associated with the growth of candida. Pain at intercourse was associated with the growth of candida and recurrent candidiasis.